Antibiotic and metal(loid) resistance of Pedobacter lusitanus NL19 and its closely-related species - Viana, Ana Teresa Torre (2019)
Pedobacter lusitanus NL19 was isolated from a sludge collected from a deactivated uranium mine, Quinta do Bispo (Viseu, Portugal). The sampling site is characterized by high levels of metals and radionuclides. In silico genome analysis of NL19 disclosed several antibiotic resistancerelated genes (β-lactamase, efflux pumps, etc.) and also genetic determinants related with the resistance/tolerance to metal(loid)s (arsenic, zinc, cobalt and cadmium). The main objective of this study was to investigate the antibiotic resistance and metal(loid)s tolerance of P. lusitanus NL19, the closely-related species P. himalayensis MTCC 6384T, P. hartonius DSM 19033T, P. cryoconitis DSM 14825T and P. westerhofensis DSM 19036T as well as the genus type strain, P. heparinus DSM 2366T. The results of disk-diffusion susceptibility testing and MIC determination showed that all the strains are resistant to amoxicillin/clavulanic acid, ampicillin, apramycin sulfate, aztreonam, cefepime, cefoxitin, ceftazidime, cefuroxime, penicillin G, piperacillin, piperacillin/tazobactam, amikacin, gentamicin, netilmicin, streptomycin, tobramycin, ciprofloxacin and colistin. Regarding the carbapenems all the strains are resistant to ertapenem and the majority were sensitive to meropenem and imipenem. The exceptions included resistance to meropenem by P. westerhofensis and decreased susceptibility to imipenem by P. himalayensis. The tolerance to metal(loid)s was tested through the determination of the MIC. P. lusitanus exhibited higher MICs than all the other strains, for copper and cadmium. P. lusitanus, P. himalayensis and P. hartonius were the most tolerant to zinc and nickel. Two genes encoding putative β-lactamases were identified in the genome of P. lusitanus NL19. The proteins encoded by these genes are novel members of class A β-lactamases (LUS-1) and subclass B3 metallo-β- lactamases (PLN-1), considering their low scores with other β-lactamases. To futher understand if these two enzymes had the ability to hydrolyse β- lactams, the genes blaLUS-1 and blaPLN-1 were expressed in E. coli (fused to an E. coli signal peptide) and MIC to β-lactams were determined. Results indicate that PLN-1 is able to degrade carbapenems and 1st, 3rd and 4th generation cephalosporins and cephamycines. However, no significant activity was detected for LUS-1. Our study shows that the multiresistance phenotype identified in P. lusitanus NL19 is also observed in its closely-related species. In addition, it seems clear that the Pedobacter genus have an underexplored pool of antibiotic resistance genes as well as putative novel antibiotic resistance mechanisms. The tolerance to metal(loid)s was more strain-specific and, therefore, it appears to be related to the ecological niches that these strains occupy.